The afterlife of Adam Smith : the influence, interpretation and misinterpretation of his economic philosophy, 1760s-2010s - Farina, William, 1955- (Jefferson, North Carolina : McFarland & Company, Incorporated, Publishers, 2015)
"Smith himself would have been surprised at the near universal acceptance of his theories, especially given changes in the world economy since the 18th century. This book provides a close reading of his work, revealing a complex intellect schooled in the high moral ideals of classical philosophy, yet firmly grounded in the pragmatism of international trade and commerce"--
Introduction -- Businessmen become revolutionaries (1764/1777) -- A new republic grapples with old issues (1778/1790) -- The british empire makes war against its offspring (1791/1815) -- Almost free labor (1816/1837) -- Might makes right (1838/1850) -- Northern industry tames southern agriculture (1851/1865) -- More competition, more oppression (1866/1877) -- The great american relocation (1878/1890) -- A clumsy foray into colonialism (1891/1901) -- Trustbuster (1901/1913) -- Anglo-american power shift (1914/1921) -- Ascendant consumerism (1922/1928) -- The implosion of ?laissez-faire (1929/1939) -- An unprecedented middle class (1941/1959) -- Military-industrial complex (1960/1975) -- Tax credit utopia (1976/1988) -- A kinder and gentler corporate mandate (1989/2000) -- Post 9-11 -- Summary -- Chapter notes -- Selected bibliography -- Index.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Smith, Adam, -- 1723-1790.; United States -- Foreign economic relations -- Great Britain -- History; Great Britain -- Foreign economic relations -- United States -- History; United States -- Economic policy; Great Britain -- Economic policy; Electronic books